2021
DOI: 10.1111/bph.15520
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical changes in brain reward status during oxycodone self‐administration in a novel test of the negative reinforcement hypothesis

Abstract: Background and Purpose: The extra medical use of, and addiction to, prescription opioid analgesics is a growing health problem. To characterize how prescription opioid abuse develops, this study investigated the affective consequences of escalating prescription opioid use using intracranial self-stimulation (ICSS) reward and oxycodone intravenous self-administration (IVSA) models.Experimental Approach: Male Wistar rats were given access to oxycodone IVSA (0.15 mgÁkg À1 per infusion, i.v.) in short-access (ShA;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 105 publications
6
15
0
Order By: Relevance
“…When nonpreference producing doses of Δ 9 -THC (3 mg/kg) and oxycodone (1 mg/kg) were administered, it resulted in the development of CPP in both sexes. These findings parallel recent literature reporting that vaporized or injected Δ 9 -THC reduces oxycodone (Nguyen et al, 2019;Nguyen et al, 2021;Nguyen et al, 2023) and heroin (Gutierrez et al, 2022) self-administration in rats. The authors in (Nguyen et al, 2021;Nguyen et al, 2023) suggest that Δ 9 -THC may be increasing the rewarding efficacy of a "unit dose" of oxycodone when self-administered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When nonpreference producing doses of Δ 9 -THC (3 mg/kg) and oxycodone (1 mg/kg) were administered, it resulted in the development of CPP in both sexes. These findings parallel recent literature reporting that vaporized or injected Δ 9 -THC reduces oxycodone (Nguyen et al, 2019;Nguyen et al, 2021;Nguyen et al, 2023) and heroin (Gutierrez et al, 2022) self-administration in rats. The authors in (Nguyen et al, 2021;Nguyen et al, 2023) suggest that Δ 9 -THC may be increasing the rewarding efficacy of a "unit dose" of oxycodone when self-administered.…”
Section: Discussionsupporting
confidence: 90%
“…These findings parallel recent literature reporting that vaporized or injected Δ 9 -THC reduces oxycodone (Nguyen et al, 2019;Nguyen et al, 2021;Nguyen et al, 2023) and heroin (Gutierrez et al, 2022) self-administration in rats. The authors in (Nguyen et al, 2021;Nguyen et al, 2023) suggest that Δ 9 -THC may be increasing the rewarding efficacy of a "unit dose" of oxycodone when self-administered. Our findings in the CPP paradigm are consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…It was somewhat unexpected that rats reached similar breakpoints for 0.06 and 0.15 mg/kg/infusion in the PR under control condi ons (PG here, also true in the notreatment acclima on sessions) given an apparent difference across this dose range that was observed in prior work with male rats trained in sessions of 1 h or 12 h dura on (Nguyen et al, 2021;Nguyen et al, 2018;Wade et al, 2015). In par cular, Wade and colleagues showed that the largest difference was between the 0.06 and 0.15 mg/kg/infusion doses in the animals trained in 12 h sessions and between the 0.15 and 0.30 mg/kg/infusion doses in the animals trained in 1 h sessions.…”
Section: Discussionsupporting
confidence: 68%
“…The theory states that KOR activity is involved in negative valence domains (e.g., acute threat, potential threat, sustained threat, loss, and frustrative nonreward) and is critical for the development of subsequent behavioral responses to aversive stimuli, such as negative reinforcement [ 12 , 22 , 25 , 42 , 43 ]. The role of KORs in these constructs are typically tested in behavioral assays such as learned helplessness [ 44 ], forced swim stress [ 18 ], stress-induced reinstatement [ 45 , 46 ], and intracranial self-stimulation [ 47 ].…”
Section: Introductionmentioning
confidence: 99%